The influence of physical instream spatial variability on Chironomidae (Diptera) assemblages in Neotropical streams - Mazao, Gustavo Rincon [UNESP]; Bispo, Pitagoras da Conceicao [UNESP] (Elsevier B.V., 2016)
In this study, the Chironomidae assemblages were studied in order to test the following hypotheses: a) mesohabitat type and substrate complexity affect the richness, abundance, and composition of the fauna; b) mesohabitat type is a good predictor for Chironomidae composition. To test the hypotheses, experiments were carried out in two mesohabitats (riffle and pool) using two substrate complexities (high and low) in 12 streams from Central Brazil. The mesohabitat type and substrate complexity did not affect the richness and abundance of the local fauna. The mesohabitat affected the faunistic composition. The assemblages of riffles and pools were distinct. Indicator Species Analysis showed that Paratendipes sp., Polypedilum sp. 2, Pentaneura sp., Rheotanytarsus sp. 1, Corynoneura sp. 2, Cricotopus sp. 2, Lopescladius sp., Nanocladius sp. 2, Parametriocnemus sp., and Thienemanniella sp. had preference for riffles and Chironomus sp., Ablabesmyia sp. 1, Ablabesmyia sp. 2, Djalmabatista sp., Fittkauimyia sp., and Labrundinia sp. for pools. Our results highlight the importance of physical instream variability on fauna structure, suggesting that habitat homogenization due to anthropic action may cause drastic effects on the diversity of chironomids and, probably, other benthic macroinvertebrates. Therefore, maintaining instream morphology, including the different mesohabitats, is fundamental for biodiversity conservation in streams. (C) 2016 Elsevier GmbH. All rights reserved.
Keywords: Diversity; Aquatic insects; Lotic environment; Cerrado